ChemInform Abstract: Synthesis and Reactivity of Triazaphenanthrenes. Issue 46 (27th October 2016) - Fernandez, Sarah; Ganiek, Maximilian A.; Karpacheva, Mariia; Hanusch, Fabian C.; Reuter, Stephan; Bein, Thomas; Auras, Florian; Knochel, Paul
Abstract: A four‐step synthesis of triazaphenanthrenes and chlorinated derivatives thereof is described.